Assessment of Teachers’ Turnover and its Impact on Academic Performance in Government Aided Secondary Schools of Kayonza Sub-County Kanungu District. - Biryomumeisho, Gideon (Kabale University, 2025)
This study examined the factors influencing teacher turnover and its impact on academic performance in government-aided secondary schools in Kayonza Sub-county, Kanungu District. The research was guided by three specific objectives: (1) To investigate the role of teacher turnover on academic performance; (2) To identify the factors affecting teacher turnover; and (3) To suggest possible solutions to the factors affecting teacher turnover. A descriptive survey design incorporating both qualitative and quantitative data was employed. The study population comprised 75 teachers from three selected secondary schools, with a sample size of 63 respondents. Data collection methods included questionnaires and interviews. The qualitative data were analyzed thematically, while the quantitative data were analyzed using SPSS software, with results presented in tables, figures, and charts. The key findings of the study revealed that high teacher turnover significantly impacts academic performance in government-aided secondary schools in the Kayonza Sub-county. Respondents indicated that the frequent changes in teaching staff disrupt the continuity of learning, weaken teacher-student relationships, and ultimately hinder students’ academic progress. Several factors were identified as contributing to teacher turnover. Firstly, low salary was cited by a significant majority (71.4%) of respondents as a primary reason for leaving. Teachers expressed dissatisfaction with their compensation, which led many to seek better-paying opportunities elsewhere. Secondly, poor working conditions were highlighted by 60.3% of respondents, who pointed to the lack of adequate teaching materials and poor infrastructure as key factors contributing to a stressful work environment. Thirdly, the lack of career advancement opportunities was identified as a significant demotivator, with 79.4% of respondents feeling that limited opportunities for professional growth and promotion pushed them to leave. Additionally, the heavy workload, including large class sizes and additional administrative duties, was noted by 66.7% of respondents as a contributing factor to their decision to leave. Lastly, inadequate support from the administration was mentioned by 55.6% of respondents, who noted that the lack of support eroded their morale and led to higher turnover rates. The study recommends several strategies to address teacher turnover, including increasing teacher salaries and benefits and improving working conditions.